2019
DOI: 10.1159/000497164
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease and Neurotransmission Gene Variants: Focus on Their Effects on Psychiatric Comorbidities and Inflammatory Parameters

Abstract: <b><i>Background:</i></b> Alzheimer’s disease (AD) is a neurodegenerative disorder accounting for 60–70% of dementia cases. Genetic origin accounts for 49–79% of disease risk. This paper aims to investigate the association of 17 polymorphisms within 7 genes involved in neurotransmission (<i>COMT</i>, <i>HTR2A</i>, <i>PPP3CC</i>, <i>RORA</i>, <i>SIGMAR1</i>, <i>SIRT1</i>, and <i>SORBS3</i>) and AD. <b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The study found that the rs4680 variant of the COMT genotype was associated with AD, and the rs174696 variant of COMT was associated with depression in Greek AD patients. Thus, the study supported the role of the rs4680 variant in the disease pathogenesis of AD [ 29 ]. Since this research was conducted on a Greek and Italian subsample, this work should be replicated among other population samples as well.…”
Section: Reviewsupporting
confidence: 71%
“…The study found that the rs4680 variant of the COMT genotype was associated with AD, and the rs174696 variant of COMT was associated with depression in Greek AD patients. Thus, the study supported the role of the rs4680 variant in the disease pathogenesis of AD [ 29 ]. Since this research was conducted on a Greek and Italian subsample, this work should be replicated among other population samples as well.…”
Section: Reviewsupporting
confidence: 71%
“…Molecules like Programmed Cell Death 5 (PDCD5) may play a role in programmed cell death observed in neurodegenerative disorders [ 111 ]. Genomic mutations in Sorbin and SH3 Domain Containing 3 (SORBS3) that may regulate cell proliferation were associated with Alzheimer’s disease [ 112 , 113 ]. Thymus, Brain And Testes Associated (TBATA) that plays a role in neurite outgrowth increased in the circulation in AD [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears vital to also acknowledge “choosing to be distant” as having implications for an agency in people living with dementia. Withdrawal from social interaction may be a consequence of the disease process ( Porcelli et al, 2019 ), but it may also be perceived as a choice even in people with more advanced dementia ( Ciofi et al, 2022 ). It appeared here that some people actively choose not to join in with group activities: physically distancing themselves from surrounding social activity, describing making a choice on when to “join in.” Without more closely investigating the intent of a person with dementia, we may ascribe their apparently more limited actions to apathy; a dementia symptom rather than their active choice.…”
Section: Discussionmentioning
confidence: 99%